Sanda Tomescu Baciu, Roxana-Ema Dreve, Raluca-Daniela Duinea, Fartein Th. Øverland, Raluca Pop (eds.), "30 Years of Norwegian Language and Literature in Romania at Babeș-Bolyai University", Cluj-Napoca: Presa Universitară Clujeană, 2021, 255 p. - TEȘU, Georgiana (Studia Universitatis Babeș-Bolyai Philologia, 2023)
Published in 2021 with a trilingual title, the collective volume 30 Years of Norwegian Language and Literature in Romania at Babeș-Bolyai University serves as a celebration of three decades of Norwegian studies at BBU’s Faculty of Letters. It incorporates official anniversary greetings from several Norwegian and Romanian institutions, personal messages from collaborators and alumni, as well as academic papers on a variety of topics revolving around Scandinavian linguistic and literary studies.